2020
DOI: 10.1097/cm9.0000000000001245
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of blood lipids and risk factors of dyslipidemia among people living with human immunodeficiency virus who had received first-line antiretroviral regimens for 3 years in Shenzhen

Abstract: Background Lipid abnormalities are prevalent among people living with human immunodeficiency virus (HIV) (PLWH) and contribute to increasing risk of cardiovascular events. This study aims to investigate the incidence of dyslipidemia and its risk factors in PLWH after receiving different first-line free antiretroviral regimens. Methods PLWH who sought care at the Third People's Hospital of Shenzhen from January 2014 to December 2018 were included, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…As previously reported, the effect of TDF + 3TC + EFV had a relatively small impact on dyslipidemia among PLWH in China. 25 This study also confirmed that TDF + 3TC + EFV was mainly associated with an increased TG level. E/C/F/TAF exposure was associated with increased TC, TG, and LDL-C levels, which was consistent with the results of the study by Huang et al 26 It is worth noting that TC, TG, and LDL-C in E/C/F/TAF group were all higher than those in TDF + 3TC + EFV group at 3, 6, 9, and 12 months of ART initiation.…”
Section: Discussionsupporting
confidence: 76%
“…As previously reported, the effect of TDF + 3TC + EFV had a relatively small impact on dyslipidemia among PLWH in China. 25 This study also confirmed that TDF + 3TC + EFV was mainly associated with an increased TG level. E/C/F/TAF exposure was associated with increased TC, TG, and LDL-C levels, which was consistent with the results of the study by Huang et al 26 It is worth noting that TC, TG, and LDL-C in E/C/F/TAF group were all higher than those in TDF + 3TC + EFV group at 3, 6, 9, and 12 months of ART initiation.…”
Section: Discussionsupporting
confidence: 76%
“…Even though there was a wide range of confounding factors and limited sample size in this study, advanced methods and sensitivity analyses were used to obtain robust analysis results. Our findings confirm and extend the results from previous observational studies, which showed that age, gender, BMI, CD4 count, and ART duration were the predictors of unfavorable lipid profiles alterations in patients on ART ( 24 , 25 , 30 , 31 ).…”
Section: Discussionsupporting
confidence: 91%
“…The median CNS toxicity score at baseline was estimated at 13 (IQR: 11-15). Compared to the baseline CNS toxicity score, the median CNS toxicity score at week 12 (which became 10 [IQR: [8][9][10][11][12]) significantly decreased (compared with baseline, P < 0.001) and remained stable at weeks 24 (9 [IQR: 7-12], P < 0.001) and 48 (9 [IQR: 7-11], P < 0.001).…”
Section: Change In Central Nervous Symptoms and Patient Selfreported ...mentioning
confidence: 95%
“…[3] A significant number of PI-related dyslipidemias have also been reported. [7][8][9][10] As such, we can note the elevation of lipid parameters like total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and triglycerides (TG), which are recognized risk factors for cardiovascular disease. [10] The fixed-dose combination, oral tablet, of elvitegravir/ cobicistat/emtricitabine/tenofovir alafenamide (E/C/F/ TAF) for HIV treatment was first approved by the US Food and Drug Administration in 2015 [11] and then officially introduced in China for the first time in 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation